Studi Eksplorasi Pembelajaran Menulis Teks Fantasi Berdasarkan Kurikulum Merdeka Siswa Kelas VII SMP - Imsa, Choirul (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The background of this study was to determine the implementation of fantasy text writing learning based on the Independent Curriculum for grade VII junior high school students in the Magelang area which includes the use of teaching materials, learning media, learning strategies and methods, and obstacles faced by teachers in learning to write fantasy texts based on the Independent Curriculum. The subjects of the study were 15 Indonesian language subject teachers from 15 schools in the Magelang area. The data taken were quantitative and qualitative data. The data collection techniques used were questionnaires and interviews. The data analysis techniques used were descriptive quantitative and qualitative. The results of the study found that 66.7% of teachers used Kemendikbud textbook teaching materials, 66.6% used LKS, 60% used lecture methods, 71.4% used power point media, 33.3% used special methods and strategies in learning to write fantasy texts. 33.3% of students were very enthusiastic in learning to write fantasy texts, 42.9% of teachers had implemented differentiated learning according to the Independent Curriculum.